2013
DOI: 10.1039/c3ta12923c
|View full text |Cite
|
Sign up to set email alerts
|

3D ordered macroporous germanium fabricated by electrodeposition from an ionic liquid and its lithium storage properties

Abstract: Among the group IVA materials, germanium has a large theoretical specific capacity, good electrical conductivity and fast lithium ion diffusivity, making it an alternative anode material for Li ion batteries.Nanostructured electrodes now are the biggest focus to solve the volume expansion problem and to improve cycling and rate performance. Ionic liquid electrodeposition was used to obtain Ge nanoparticles at room temperature, and by combining with a "hard" template, 3D macroporous frameworks have been easily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 32 publications
2
36
0
1
Order By: Relevance
“…For this experiment, the deposition potential was maintained at about À 1.47 V for 30 min. These results are similar to those reported for Ge deposited on Cu foil [21] and indicate that the CNTs are of high quality and provide good electrical conductivity. Fig.…”
Section: Methodssupporting
confidence: 92%
“…For this experiment, the deposition potential was maintained at about À 1.47 V for 30 min. These results are similar to those reported for Ge deposited on Cu foil [21] and indicate that the CNTs are of high quality and provide good electrical conductivity. Fig.…”
Section: Methodssupporting
confidence: 92%
“…This approach is ilustrated in a number of recent studies utilizing porous Ge NPs or a nanoporous Ge network [57][58][59][60][61], which were prepared from simple (e.g. mechanochemical synthesis) to often-complicated synthesis (e.g.…”
Section: Three-dimensional Porous Gementioning
confidence: 99%
“…In a similar study, Ge NPs were electrodeposited at room temperature in PS templates to form a 3D ordered mesoporous Ge with a highly crystalline phase. , for 0.05C, 0.2, and 0.5C, respectively, after 600 cycles [61]. The authors argue that the superior performance of the porous GeOx anode arises from the synergy of the material's four characteristics: small primary particles, porous structure, amorphous state, and the incorporation of oxygen.…”
Section: Three-dimensional Porous Gementioning
confidence: 99%
“…[18][19][20][21][22][23][24][25] Nevertheless, the practical application of Ge is hindered by the pulverization problem caused by the large volume changes during Li insertion/extraction processes, thus leading to the loss of electrical conductivity and consequently a rapid capacity decline upon cycling. [26][27][28][29][30][31] Previously studies have demonstrated that decreasing the Ge particle size into the nanometer range could alleviate the stress produced during Li uptake and release processes and suppress the tendency of the nanostructure to fracture. [32][33][34][35] Moreover, the nanostructure can facilitate the diffusion of Li ion, resulting in high rate capability.…”
Section: Introductionmentioning
confidence: 99%